Environmental awareness in information technology adoption and consumer intention to support green businesses: Research agenda for empirical study - Kurkoon, Pakvalit; Pimchangthong, Daranee; Boonjing, Veera (My University, 2016)
This agenda scrutinizes the individual perspective and awareness of environmental impact when purchasing and using IT products, the influence of society on IT-product use, the individual's attitude towards green-imaged businesses and the influence of green-imaged business policies. This study referenced communication theories and information system success models as the basis to break down the framework into three phases; Green IT Introduction, Green Individual Acceptance and Green Organizational Impact. This agenda suggests that a consumer will purchase or use environmentally friendly IT products if he/she acknowledges the benefits of protecting and preserving the environment while being willing to spend more money and time, accept reduced product capability and understand the meaning of eco-labels. In addition, the role that peers and superiors play in individual decisions and awareness of which behaviors damage the ecosystem are also elements. Moreover, how willingness to purchase or use green IT product leads to the support of green-imaged businesses.
Keywords: Environmental policy; Green business; Green consumer; Green image; Green IT; Green IT adoption; Green IT product; Green policy; Green reputation